The Influence of Parent Pairs with Different Genetic Distances on the Genetic Diversity of Offspring in Strongylocentrotus intermedius - Peng Liu; Xuechun Jiang; Hao Guo; Tongshan Jia; Shuaichen Wu; Fanjiang Ou; Wenzhuo Tian; Lei Liu; Yaqing Chang; Jun Ding; Weijie Zhang (Biology, 2025)
To identify effective strategies for preserving the genetic diversity of Strongylocentrotus intermedius populations, this study employed 15 SSR loci and SSR-seq technology to construct three parental mating groups based on different genetic distances: relatively distant (0.33640), relatively close (0.13051), and mixed (0.29916). These mating groups were used to produce three corresponding offspring populations: the distant group (D), the close group (C), and the mixed group (M). A total of 150 offspring from these populations were genotyped to analyze the effects of parental genetic distance on the genetic diversity of their offspring. The results showed that the observed allele number (Na) in the D and M groups was 4.200 and 4.733, respectively, both lower than the parental family population (FP) group (5.000) but higher than the C group (3.571). The effective allele number (Ne) in the D and M groups was 2.782 and 2.728, respectively, slightly below that of the parental FP group (2.816) but greater than the C group (2.211). Similarly, the observed heterozygosity (Ho) in the D and M groups was 0.496 and 0.488, respectively, both below that of the parental FP group (0.522) but above the C group (0.447). The expected heterozygosity (He) in the D and M groups was 0.586 and 0.579, respectively, slightly lower than the parental FP group (0.595) but higher than the C group (0.487). Additionally, the polymorphism information content (PIC) in the D and M groups was 0.530 and 0.531, respectively, indicating high polymorphism, although slightly lower than the parental FP group (0.546) and significantly higher than the C group (0.438). These findings indicate that the genetic diversity of all the three offspring populations declined to varying degrees compared to the parental population, with the C group experiencing the most severe reduction. In contrast, the D and M groups maintained comparably higher levels of genetic diversity, which were comparable to each other. This study underscores the importance of increasing the genetic distance between parents or adopting mixed mating strategies to sustain genetic diversity in breeding populations. These approaches are recommended for future breeding programs to ensure the long-term conservation and sustainability of genetic resources.